Rise of the robots technology and the threat of mass unemployment - Ford, Martin (2015 One World Publications, 2016)
In today's fast-paced world, it's tough to find the time to read. But with Joosr guides, you can get the key insights from bestselling non-fiction titles in less than 20 minutes. Whether you want to gain knowledge on the go or find the books you'll love, Joosr's brief and accessible eBook summaries fit into your life. Find out more at joosr.com.
Includes index
Keywords: Technology